Effects of Different Environment-Friendly Gibberellic Acid Microcapsules on Herbicide Injury of Wheat - Zhang, Guisen; Ma, Tao; Cheng, Yong; Wang, Jianing; Liu, Lang; Zhang, Baojun (Frontiers in Plant Science, 2022)
Environmentally friendly microcapsules are becoming more and more widely used due to the increasing demand for environmental safety in pesticides. To compare the impact of differences in wheat herbicide phytotoxicity of different gibberellic acid microcapsule suspensions, two microcapsule suspensions were separately formulated using the phase transfer method and the in situ polymerization method, and the key performance indicators are the size of microcapsules and the degree of encapsulation. Meanwhile, through field trials, the pharmacological and detoxification effects of different types of microcapsule suspensions on the herbicide methyldisulfuron in wheat fields were compared. The microcapsule suspension was prepared by the phase transfer method and the particle sizes D10, D50, and D90 are 0.990, 2.136, and 5.201 μm, respectively; the microcapsule suspension was prepared by the in situ polymerization, the particle sizes D10, D50, and D90 are 4.365, 8.547, and 16.782 μm, respectively. The encapsulation rate of the microcapsules prepared by the phase transfer method and the in situ polymerization method was 86.9% and 91.2%, being higher than 80%, the national standard for capsules. Meanwhile, the release rate conforms to first-order release kinetics in 0–4 days and zero-order release kinetics in 5–28 days. The plot trials' result showed that the detoxification effect of the microcapsules prepared by the in situ polymerization method was significantly better than the detoxification effect of the microcapsules prepared by the phase transfer method and the control agent. The growth index of wheat was higher than that of the untreated check after using the agent.